The Correlation Between The Student’s Learning Outcomes In “F&B Service” And Student’s Interest In Joining LKS Restaurant Service At SMK Negeri 6 Padang - Azis, Rizky Pratama; Elida, Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This study started from the researcher's observations of students of SMK Negeri 6 Padang whose learning outcomes were in the subject of F&B Service but low interest in participating in the Restaurant Service LKS, this led to a decline in learning achievement of SMK Negeri 6 Padang. in LKS activities. This study aims to: 1) Describe student learning outcomes in the subject of cuisine; 2) Describe students' interest in participating in LKS Restaurant Service; 3) Analyzing the relationship between student learning outcomes of F&B Service with student interest in participating in the Restaurant Service LKS at SMK Negeri 6 Padang. This type of research is descriptive correlational research with a quantitative approach. The sample of this research was 101 students of class XII culinary at SMK Negeri 6 Padang. The sampling technique used is a saturated sample. Research data collection was carried out using a questionnaire designed based on a Likert scale that had been tested for validity and reliability. Furthermore, the data obtained were analyzed by data description tests, correlation tests, and hypotheses. The results of the description of the results of learning cooking cuisine are in the medium interval class with a total of 52 respondents (51.48%), while the interest in participating in the Restaurant Service LKS is in the medium category with a total of 46 (45.54%). Furthermore, the normality analysis test of the data obtained was normally distributed with a value of 0.176> 0.05, while the linearity analysis of the data obtained was linearly distributed with a value of 0.343> 0.05. The correlation test shows that 0.471 is categorized as moderate according to the interpretation value of r. It is known that the significance value is 0.002 <0.05, which means that there is a significant positive relationship between the Learning Outcomes variable and interest in participating in the LKS. While the value of R Square is 30% where the rest (100% -30% = 70%) is influenced by other variables outside this regression equation or variables that are not examined. The results of the t-test indicate that the known T-count is 1.760, thus Tcount > Ttable (1,760 >1,660) statistically H0 is rejected and Ha is accepted, meaning that the first hypothesis in this study is accepted.